PERCEVEJOS (HEMIPTERA: HETEROPTERA) COLETADOS EM ACEROLEIRA (MALPIGHIA GLABRA L.) EM JABOTICABAL, SP - Michelotto, M.d.; Silva, R.a. Da; Busoli, A.c. [UNESP] (Instituto Biológico, 2022)
IN JABOTICABAL, SP, BRAZIL. The objective of this work was to verify the occurrence of stinkbugs on Barbados cherry plants (Malpighia glabra L.), between 2002 and 2004, in Jaboticabal, State São Paulo, Brazil. Eleven species were colected: 7 species of Coreidae, 3 of Pentatomidae and 1 of Scutelleridae. The species Acanthocephala sp., Hyalynemus sp., Machtima crucigera (Fabricius), Euschistus atrox (Westwood), Loxa deducta and Piezodorus guidinii (Westwood) are reported for first time on Barbados cherry plants.

O objetivo deste trabalho foi avaliar a diversidade de espécies de percevejos em acerola (Malpighia glabra L.), entre 2002 e 2004, em Jaboticabal, SP. Foram coletados exemplares de 11 espécies de percevejos, sendo 7 espécies de Coreidae, três de Pentatomidae e uma de Scutelleridae. As espécies Acanthocephala sp., Hyalynemus sp.,Machtimacrucigera (Fabricius), Euschistus atrox (Westwood), Loxa deducta e Piezodorus guidinii (Westwood) são relatados pela primeira vez ocorrendo em plantas de aceroleira.
STINKBUGS (HEMIPTERA: HETEROPTERA) COLLECTED ON BARBADOS CHERRY PLANTS (MALPIGHIA GLABRA L.) IN JABOTICABAL, SP, BRAZIL
Keywords: Leptoglossus sp.; Crinocerus sanctus; Pachycoris torridus; Leptoglossus sp.; Crinocerus sanctus; Pachycoris torridus